2019
DOI: 10.35536/ljb.2019.v7.i2.a5
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Price and Promotion in Creating Brand Equity

Abstract: The purpose of this study is to ascertain the influence of price and promotion on brand equity, which eventually leads to the determination of consumer’s preference for a particular brand. This research aims to add value to the current field by testing this relationship under the influence of three other mediating dimensions including the brand image, brand loyalty and quality of the product. In order to test the proposed model, the Structural Equation Modeling technique was used in this study. Within this rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Studies have revealed that the gut microbiota in people with Parkinson's disease differs from those in health, with a reduced number of helpful bacteria and a larger abundance of possibly dangerous bacteria [71]. The course of Parkinson's disease is assumed to be aided by increased inflammation due to the alterations in gut microbiota in another research [72]. A high-fiber diet was linked to a lower incidence of Parkinson's disease, according to research on food [73].…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…Studies have revealed that the gut microbiota in people with Parkinson's disease differs from those in health, with a reduced number of helpful bacteria and a larger abundance of possibly dangerous bacteria [71]. The course of Parkinson's disease is assumed to be aided by increased inflammation due to the alterations in gut microbiota in another research [72]. A high-fiber diet was linked to a lower incidence of Parkinson's disease, according to research on food [73].…”
Section: Parkinson's Diseasementioning
confidence: 99%